Urban Farming di Permukiman Pesisir untuk Mendukung Ketahanan Pangan Rumah Tangga - Sri Aliah Ekawati (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2023)
Food security and sustainable cities and communities are issues of sustainable goals which are heavily influenced by the conditions of the COVID-19 pandemic. The coastal settlements of the Tallo Subdistrict, which are mostly inhabited by people with a low economic class and work in the informal sector, cannot avoid the economic impact of post-COVID-19. The decline in people’s income has resulted in a decrease in spending on vegetable consumption. In addition, the conditions of dense coastal settlements and lack of green space make urban farming a solution that can be applied to solve the two problems that occur. This Community Service Program includes preparation, implementation and evaluation. The results achieved from this program are increasing community knowledge and understanding regarding urban farming. The harvest from the garden can be consumed by family members, thereby reducing spending on vegetables. It is hoped that in the future, the community will receive training related to how to process crops so that they can provide economic benefits for the local community.